Stabilization, safety, and security of distributed systems 13th International Symposium, SSS 2011, Grenoble, France, October 10-12, 2011 : proceedings - Défago, Xavier (Heidelberg Springer Berlin Heidelberg, 2011)
This book constitutes the proceedings of the 13th International Symposium on Stabilization, Safety, and Security of Distributed Systems, SSS 2011, held in Grenoble, France, in October 2011. The 29 papers presented were carefully reviewed and selected from 79 submissions. They cover the following areas: ad-hoc, sensor, and peer-to-peer networks; safety and verification; security; self-organizing and autonomic systems; and self-stabilization.
Keywords: Self-stabilization (Computer science) -- Congresses; Electronic data processing -- Distributed processing -- Safety measures -- Congresses; Computer security -- Congresses; Electronic books